Differential sodium current remodelling in human left atrial appendage cardiomyocytes in paroxysmal and persistent atrial fibrillation. (19th May 2022) - Casini, S; Marchal, GA; Kawasaki, M; Fabrizi, B; Wesselink, R; Nariswari, FA; Neefs, J; Van Den Berg, NWE; Driessen, AHG; De Groot, JR; Verkerk, AO; Remme, CA
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is characterized by complex electrical, structural and metabolic remodelling. The mechanisms underlying AF progression from paroxysmal to persistent AF are not fully understood, and studies in cardiomyocytes (CMs) at the paroxysmal stage of AF are lacking. Moreover, most studies have so far investigated right atrial appendage CMs, while left atrial appendage (LAA) CMs may be more informative, as AF is predominantly a left atrial disease. Whether and to what extent electrical remodelling during various AF stages also includes alterations of the (late) sodium current (INa), remains unclear. Moreover, the functional relevance of sodium channel isoforms other than the cardiac Nav1.5, such as the "neuronal" isoform SCN10A/NaV1.8, during the various stages of AF is as yet not fully elucidated. Purpose: To investigate peak and late INa remodelling in LAA CMs from patients with paroxysmal and persistent AF and patients in sinus rhythm (SR), as well as the potential contribution of NaV1.8-based current. Methods: LAA were obtained from patients in SR (N=18) without a history of AF undergoing cardiac surgery, as well as from patients with paroxysmal (N=12) and persistent AF (N=30). Paroxysmal AF was defined as AF episodes terminating spontaneously within seven days and persistent as AF continuing for more than 7 days but less than 1 year. Peak INa, late INa and action potential (AP) properties were investigated through patch-clamp analysis on single LAA CMs, while qPCR was used to assess SCN5A and SCN10A expression levels in LAA tissue. Results: In paroxysmal and persistent AF CMs, AP duration was shorter than in SR CMs. Compared to SR, peak INa (Figure 1A) and SCN5A expression (Figure 1B) were significantly decreased in paroxysmal AF, while they were restored to SR levels in persistent AF. Conversely, while late INa was undetectable in SR and paroxysmal AF, it was significantly increased in persistent AF (Figure 2). Peak and late INa Nav1.8-based current was not detected in persistent AF CMs. Similarly, expression of SCN10A was not observed in LAAs at any stage. Conclusions: Our study is the first to show that AP shortening already occurs in LAA CMs from paroxysmal AF, potentially contributing to pro-arrhythmia in this early stage of the disease. Moreover, our findings demonstrate that INa is differentially remodelled during various stages of AF, with peak INa reduction occurring during paroxysmal AF, while late INa is increased in persistent AF only. Finally, we have shown that Nav1.8 current does not contribute to the AF-related alterations in INa. These observations are of particular relevance when considering potential pharmacological approaches targeting (late) INa in patients with distinct forms of AF.